Electrocaloric enhancement near the morphotropic phase boundary in lead-free NBT-KBT ceramics - Le,Goupil F; Bennett,J; Axelsson,A-K; Valant,M; Berenov,A; Bell,AJ; Comyn,TP; Alford,NM (Applied Physics Letters, 2015)
The electrocaloric effects (ECEs) of the morphotropic phase boundary (MPB) composition 0.82(Na0.5Bi0.5)TiO3-0.18(K0.5Bi0.5)TiO3 (NBT-18KBT) are studied by direct measurements. The maximum ECE ΔTmax = 0.73 K is measured at 160 °C under 22 kV/cm. This corresponds to an ECE responsivity (ΔT/ΔE) of 0.33 × 10−6 K m/V, which is comparable with the best reported values for lead-free ceramics. A comparison between the direct and indirect ECE measurements shows significant discrepancies. The direct measurement of both positive and negative electrocaloric effect confirms the presence of numerous polar phases near the MPB of NBT-based materials and highlights their potential for solid-state cooling based on high field-induced entropy changes.